Química de otólitos da cavala-empinge (Acanthocybium solandri) no Oceano Atlântico - Andrade, Thays Freitas de (2024)
The Wahoo, Acanthocybium solandri (Cuvier, 1832), is a marine epipelagic species that occurs in subtropical and tropical environments in the Atlantic, Indian, and Pacific oceans. There are no observations of large schools of A. solandri, being a species of solitary habits, although it can form small groups. Despite having exploited stocks in several areas around the world, it is classified as Least Concern (LC) on the International Union for Conservation of Nature (IUCN) Red List of Threatened Species. Research using otolith chemistry has been developed in recent decades, including fish from the Scombridae family, but unpublished with A. solandri. The objective of this study was to analyze the chemical composition of the edge of the otolith of 30 individuals of the species A. solandri, the concentrations of Strontium (Sr), Barium (Ba). Magnesium (Mg) and Manganese (Mn) were obtained using the LA-ICP-MS technique as a way to identify differences between different fishing stocks in the Atlantic Ocean. The samples in this study were collected in three different locations in the Atlantic: Brazil, Canary Islands and Ivory Coast. Clear patterns were identified regarding the concentration of Ba and Sr related to the collection environment, with low concentrations of Ba and high concentrations of Sr. The upwelling that occurs in the region in the Spanish archipelago of the Canary Islands due to the Canary Current system made the characterization different from the individuals collected in Brazil. The point upwelling that occurs in the Ivory Coast also influenced the concentration of Ba in the region. This upwelling and the smaller sizes recorded for the individuals in this region show us a possible nursery area for the species. The concentrations of Mg and Mn behaved differently on the edge of the otoliths of all regions, making it impossible to infer a bias about their results.